Seasonal variability in chemical composition and source apportionment of sub-micron aerosol over a high altitude site in Western Ghats, India. (May 2018) - Mukherjee, Subrata; Singla, Vyoma; Pandithurai, Govindan; Safai, P.D.; Meena, G.S.; Dani, K.K.; Anil Kumar, V.
Abstract: This manuscript reports the seasonal variation of chemically speciated sub-micron aerosol particles (diameter < 1 μm). An Aerosol Chemical Speciation Monitor (ACSM) was used to measure the mass concentration of non-refractory particulate matter (NR-PM1 ) at a high-altitude site in the Western Ghats, India from March 2016 to February 2017. The mass concentration of NR-PM1 averaged at 7.5 ± 6.5 μgm –3, with major contributions from organics (59%) and sulfates (23%). Positive matrix factorization (PMF) was applied on the measured mass spectra of organic aerosol (OA) to derive the sources distinctive of each season (Summer, Monsoon, Post-Monsoon and Winter). The four OA factors (two primary OA and two oxygenated OA) resolved during summer, post-monsoon and winter season. However, only one oxygenated factor resolved during monsoon and contributed only 20% to the total OA. The factors associated with primary emissions dominated during the monsoon, whereas factors related to secondary formation dominated in other three seasons. During summer, an isoprene derived SOA – IEPOX-OA (isoprene-epoxydiol OA) contributed ∼17% to the total OA. Cluster and concentration weighted trajectory (CWT) analyses were performed to identify the possible source regions of NR-PM1 mass concentration observed at the receptor site. The analysis identifies Central India as the potential source region of transported aerosol during post-monsoon and winter season. Our study suggests that contributions from both local sources and regional transport are important in governing mass concentration of PM1 over Mahabaleshwar. Graphical abstract: Image 1 Highlights: Organics dominated the NR-PM1 aerosol fraction with >55% during all seasons. The primary emissions (>75%) dominated organics aerosol fraction during monsoon. IEPOX-OA deconvolved during summer with the contribution of 17% to total OA. The cluster and CWT analyses identified Central India as the potential source region.